Integrated Experimental and Thermodynamic Modelling Study of the Multicomponent “Cu2O”-FeO-Fe2O3-CaO-SiO2-PbO-ZnO-Al2O3 System - M. Shevchenko; V. Prostakova (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
The copper smelting gas / slag / matte / metal / solids system with the Cu-Fe-Ca-Si-O-S major elements has been a long-term focus of the present overall research program using integrated experimental and modelling approach for the phase equilibria characterisation and development of a thermodynamic database. A systematic investigation of phase equilibria of slag systems in equilibrium with Cu metal is providing information for systems where copper coexists in slag with lead, zinc, and aluminium oxides as major components. Experimental studies involve high-temperature equilibration of synthetic samples; rapid quenching; and measurement of the compositions of equilibrium phases using electron probe X-ray microanalysis (EPMA). Particularly important feature of the present study a wide range of temperatures (660-1670°C) being characterised that reveals major inconsistencies in the existing thermodynamic description of the multicomponent system, and allows to establish the thermodynamic properties from phase equilibria in a reliable way. FactSage-based thermodynamic modelling is integrated with experimental research. Initial thermodynamic assessments are used to identify priorities for experiments, planned to provide specific data for thermodynamic optimisation. Significant improvement in the accuracy of the phase equilibria description is achieved, in particular in the PbO-Cu2O-SiO2, ZnO-Cu2O-SiO2, and Cu2O-CaO- Al2O3 systems in equilibrium with metallic Cu. INTRODUCTION Slags high in lead and copper are generated in primary metal production in the smelting of lead sulfide concentrates and in pyrometallurgical metal recycling systems. The compositions of these slags are varied due to increased fraction of recycled materials in the feed as well as introduction of previously unused chemical elements to modern technology. Therefore, their processing becomes chemically more complex; in that way they contain a large number of different metals. These slags form complex non-ideal solutions (with possible formation of several immiscible slags) that can coexist with stoichiometric solids, solid solutions, mattes and molten metal depending on the bulk composition and process conditions. Predicting the outcomes of smelting and refining processes is becoming increasingly difficult. To assist in the optimisation of these metallurgical processing operations, a comprehensive research program is underway to develop accurate thermodynamic databases for these non-ferrous process systems.